STABILITY EVALUATION AND DESIGN SUPPORT OF TUNNEL ACCESS RAMP UP 4 CENTRAL CIURUG L450 PT. ANEKA TAMBANG TBK UBPE PONGKOR. - Yatjong, Isramyano
Tunnel access ramp up 4 central mine Ciurug L450 is a tunnel of transportation production with the aim of connecting the Ramp Down Central Level 450 to cross cut leading to the ore bodies later. Type supporting applied to the tunnel advances in the form of split set 1,40 m long, spaced 1,0x1,0 m2 square pattern on the roof and half the height of the wall, wiremesh type of chain-link of 2,0x4,10 m2 dimension and a steel strap (distance each 2,0 m). Discontinuous field presence and influence of excavation orientation also affect the stability of the openings. Empirical methods, analytical-numerical methods and methods of observation as an evaluation approach and design stability support openings. RMR89 based systems, the rock mass classes for segments 1 and 2 include the class II (good rock), with an average RMR value by 74 while the third segment includes class III (fair rock) with RMR corrected by 58. Q system provides quality results rock mass "good" with a Q value of 25. The results of evaluation based on monitoring data convergent-meter of tunnel segment 1 and segment 2 in a stable condition. The results of evaluation based on numerical models using UDEC v.02.1 with the conditions that applied to the design model has a displacement value of <8 mm (segment 2 and segment 3) and a stable category. The value of strength factor and the factor of safety generated above 1,20 (stable category and relative stable). The proposed design support by installing seven pieces of split set diameter 39 mm, length 1,40 m, spacing 1,0x1,0 m2 with square patterns provides condition was stable and wiremesh used. Patterns supporting qualified team of geotechnicalxPongkorxsafetyxrequirements.